THE ANALYSIS OF PERFORMANCE MEASUREMENT FOR CUSTOMER RELATIONSHIP MANAGEMENT IN THE STRATEGICS PERSPECTIVE - Febriansyah (JIPOWER : Journal of Intellectual Power, 2025)
ABSTRACT Customer relationship management (CRM) is the set of procedures, personnel, and technology used by businesses to locate their customers. CRM fosters relationships and customer retention. The development of CRM is positively impacted by organizational improvements in customer-centric procedures and advancements in information technology. Successful CRM implementation will increase an organization's profitability and customer loyalty. Viewing CRM as a technology alone is one factor contributing to its failure; in order for it to succeed, firms must integrate and strike a balance between people, process, and technology. The influence of environmental factors, such as political, economic, social, and technological aspects, on CRM is attempted to be measured. Additionally, a SWOT analysis is conducted, and a few recommendations are made based on the analysis to ensure the effectiveness of CRM activities. Key words : Measuring performance, customer relationship management, strategics perspective